2003
DOI: 10.1108/00070700310511609
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the brand on perceived quality of food products

Abstract: The chosen marketing strategy (including the branding as its integral parts) is highly important in this process. Nowadays, the brand becomes one of the basic motives for the consumers' choice of a particular food product. The importance of the product brand shall be seen primarily in its impact on consumers' choice and their loyalty through identifying and differentiating quality and origin, as well as creating additional values. The aim of this paper is to research the extent to which the consumer perceives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 10 publications
1
66
0
3
Order By: Relevance
“…A product with greater brand image is likely related to better quality and higher value [45], thus shaping a positive spiritual image [46]. This symbolic meaning facilitates consumers to support the brand to express their self-identities [47,48], and further influencing one's brand attitude, purchasing frequency and brand loyalty [49][50][51].…”
Section: Green Brand Imagementioning
confidence: 99%
“…A product with greater brand image is likely related to better quality and higher value [45], thus shaping a positive spiritual image [46]. This symbolic meaning facilitates consumers to support the brand to express their self-identities [47,48], and further influencing one's brand attitude, purchasing frequency and brand loyalty [49][50][51].…”
Section: Green Brand Imagementioning
confidence: 99%
“…2, No. 2, Sept. 2015 si cabe; los consumidores no destinan mucho tiempo a la elección de este tipo de productos y confían en unas pocas señales, como la marca, que permite valorar la calidad global (Jones & Morgan, 1994;Ozretic-Dosen, Skare & Krupka, 2007;Li, Boyd & Pai, 2011) y la seguridad (Manning, 2007;Chrysochou, 2010), valorando en segundo lugar cuestiones como las características organolépti-cas o el packaging (Vranesevic & Stancec, 2003).…”
Section: Objetivos Del Estudio Y Fundamentos Teóricosunclassified
“…The brand creates an image of the product in the consumers' mind that is associated with quality, and informs the market of the product's uniqueness in general, or in relation to other competing products (Vranesvic & Stancec, 2003). Wood and Pierson (2006, p.904) have suggested that the success of brand development may depend on the approach taken to brand description to indicate the use of the marketing mix to position a brand in the market.…”
Section: A Conceptual Framework For Product Positioning and Global Brmentioning
confidence: 99%